PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA RODA PINTAR BERKANTONG TERHADAP HASIL BELAJAR MATEMATIKA - Silviana Nur Faizah; Lia Nur Atiqoh Bela Dina; Eddy Sutadji; Erika Nur Hayati; Aynin Mashfufah (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2023)
Mathematical learning innovation demands teachers to equip students with mathematical literacy in the industrial era 4.0. This study aimed to determine the effect of the STAD-type cooperative learning model assisted by Roda Pintar Berkantong media on mathematics learning outcomes. The implementation of the quantitative method of the One Group Pretest-Posttest design in this study was supported by observation instruments, interviews, tests (pretest and posttest), and documentation (RPP). Then the data were analyzed using the scoring technique, mean, N-Gain, to test the research hypothesis and the normality test was carried out, followed by the Wilcoxon test. The results showed that the learning outcomes of the posttest (77.75) > the learning outcomes of the pretest (62.5) with an increase in learning outcomes (N-Gain) in the moderate category (0.49). Wilcoxon test results showed Asymp. Sig. 2-tailed (0.000) < 0.05 indicates that the STAD-type cooperative learning model assisted by Roda Pintar Berkantong media significantly affects the mathematics learning results on geometric material